PERLINDUNGAN HUKUM TERHADAP JUSTICE COLLABORATORDALAM KASUS PEMBUNUHAN BERENCANA (Studi Pada KasusRichard Eliezer) - Gagah Putra Perdana; Rahtami Susanti (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2023)
Justice Collaborator is often interpreted as “Crown Witness”. The case of the premeditated murder of BrigadierNofriansyah Yosua Hutabarat in 2022 became a hot topic of conversation among the Indonesian people,involving high-ranking police officers and their aides, one of the perpetrators, namely Richard Eliezer, thenventured to volunteer to become a Justice Collaborator to reveal the facts about the premeditated murderincident. the. Justice Collaborator usually reveal certain crime cases that are categorized as extraordinarycrimes or extraordinary crimes in Indonesia, where Justice Collaborator play an important role, especiallyassisting law enforcers such as investigators and public prosecutors, from the process of investigation,investigation, to examination at trial, witnesses play a role is so important that it is often the determiningreason when uncovering the case. The type of research used in this study is Normative Juridical research whichbases its analysis on Law Number 31 of 2014 Concerning the Protection of Witnesses and Victims, Article 340of the Criminal Code, and Supreme Court Circular Letter Number 4 of 2011 which is valid and relevant to thelegal issues that become focus of research Legal protection for Justice Collaborator in premeditated murdercases. Legal protection is a form of service that must be provided by the government to provide a sense ofsecurity to every citizen. LPSK provides full protection for Richard Eliezer in protecting Richard Eliezer duringthe trial process. all the things he knows about a problem, be it who is the main actor and so on, so that the casebecomes clear.